Potassium Persulfate/Tributylamine-Mediated Alkylation/Annulation of N-Arylacrylamides with Alkyl Iodides - Chen, Huimin; Sun, Zetian; Yang, Hui; Mao, Fenghua; Yan, Xinhuan; Li, Xiaoqing; Xu, Xiangsheng (Synlett, 2022)
We report a catalyst-free method for the alkylation/annulation of N-arylacrylamides to give the corresponding 3-alkyl-2-oxo-2,3-dihydro-1H-indoles by using alkyl iodides as precursors of alkyl radicals. These reactions occur at moderate temperatures and are mediated by easily accessible K2S2O8 and Bu3N.
Keywords: arylacrylamides; cyclization; oxindoles; halogen-atom transfer; alkylation